A parceria público privada nos presídios: o caso do complexo prisional da cidade de Ribeirão das Neves (MG) - Tucci Junior, Cláudio (2021)
This research addresses the management of prisons from the perspective of attempted reform for the current inefficient Brazilian prison system, with the various social problems, in addition to rebellions, escapes, corruption, inefficiency in recovery, institutionalization of organized crime - factors that prevent the adequate return of the convict to social life. A public private partnership in prisons appears as a proposal and is configured as a complement to the control of the State that intends to resize the excessive and ineffective punishment of imprisonment attributed to the State. This complementation seeks to find greater efficiency in the management of public affairs in partnership with the private initiative (PPP), proposing a possible solution to the problems currently encountered. Based on this premise, the continuation of the incarceration policy is admitted, however, now, with emphasis on the internal pacification of prisons. An adequate proposal for prison management and also to have and be ensured the treatment appropriate to those incarcerated concerns a change in criteria, but also to the new forms of prison management that considers the participation of organized prisoners, even if in illegal ways. Analyzing the effectiveness of the private administration of the Prison Complex of the City of Ribeirão das Neves (MG)